Negative Effect of Cigarette Smoke: Black Garlic Opportunities for Prevention of Ovulation Disorders - Asih, Sari Wulan; Nurseta, Tatit; Handono, Kusworini; Yudhanto, Hendy Setyo (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2024)
Women's issues are primarily related to infertility. This study aimed to demonstrate that ovarian healing in wistar rats exposed to cigarette smoke was impacted by the administration of extracted black garlic. This research uses True Experimental methods in vivo in the laboratory to identify the cause and effect of the variables being tested. This method involves replication, randomization, and control. The design chosen was a post-test-only control group design, where the experimental group received treatment and the control group did not, without random selection. The results of the study showed that there was no effect due to exposure to cigarette smoke with an increase in cortisol and a decrease in the number of secondary follicles in the ovaries of female wistar rats as well as the administration of Black Garlic (Allium sativum) extract. Black garlic extract unaffected cortisol levels and the number of secondary follicles or repair of the ovaries due to exposure to cigarette smoke. Further research is needed in dosing black garlic extract or combining it with other ingredients to provide effective results.